Pengaruh Brand Image dan Persepsi Harga Terhadap Kualitas Pelayanan dan Kepuasan Pelanggan (Studi pada Pelanggan Datsun Nissan Martadinata) - Junior, Oscar Marco Sanny; Areros, William A.; Pio, Riane J. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The immediate objectives of this research is to determined the effect of (1) Brand Image towards Service Quality on Datsun Nissan Martadinata customers, (2) Brand Image towards Customer Satisfaction on Datsun Nissan Martadinata customers, (3) Price Perception of Service Quality on Datsun Nissan Martadinata customers, (4) Price Perception of Customer Satisfaction on Datsun Nissan Martadinata customers, and (5) Service Quality towards Customer Satisfaction on Datsun Nissan Martadinata customers. The quantitative research is adapted as the method in this study and used questionnaire as the reflection of its method. Datsun buyers at Nissan Martadinata Manado are used as the population and Datsun customers are used as the samples. The questionnaires will be distributed with purposive sampling method. This study uses SmartPLS software to assist the Partial Least Square (PLS) analysis. The study resulted in 3 hypotheses were rejected from 5 hypotheses.